Dynamic performance enhancement of a grid-connected wind farm using doubly fed induction machine-based flywheel energy storage system - Taj, T.; Hasanien, H.; Alolah, A.; Muyeen, S.M. (2015)
This paper presents the dynamic performance enhancement of a wind farm connected to an IEEE-39 bus New England test system using doubly-fed induction machine (DFIM)-based flywheel energy storage system (FESS). The variable wind speed causes fluctuations in the output power of the wind farms. The use of FESS smoothes the power of the wind farm and improves the dynamic response of the system during fluctuating wind speeds. A DFIM-based FESS is proposed in this study which works on an effective control technique. The cascaded black-box optimization technique based proportional-integral (PI) control strategy is implemented on the FESS. The PI controllers are used to control the insulated gate bipolar transistor (IGBT) based rotor side converter (RSC) and the grid side converter (GSC) of the DFIM. The PI controller In-depth modeling and control strategy of the system under study is presented. The effectiveness of the proposed system is tested under real-time wind speed data. The validity of the system is verified by the simulation results which are carried out using PSCAD/EMTDC.